2005
DOI: 10.1364/ao.44.002652
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigations of birefringent holey fibers with a triple defect

Abstract: We have manufactured and characterized a birefringent holey fiber of a new construction. The birefringence in this fiber is induced by the highly elliptical shape of the core, which consists of a triple defect in a hexagonal structure. Using a hybrid edge-nodal finite-element method, we calculated the spectral dependence of phase and group modal birefringence for spatial modes E11 and E21 in idealized and in real fiber, whose geometry we determined by using a scanning-electron microscope. Results of our calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Thanks to the flexibility for the cross section design, photonic crystal fibers (PCFs) [1][2][3][4][5][6][7][8][9] have achieved excellent properties in birefringence [10][11][12][13][14][15][16][17][18][19], dispersion [20][21][22][23][24][25][26][27][28][29], single polarization single mode [30][31][32], nonlinearity [33], and effective mode area [34][35][36], and also excellent performances in the applications of fiber sensors [37,38], fiber lasers [39][40][41] and nonlinear optics [42][43][44][45] over the past several years. Large numbers of research papers have highlighted some optical properties of the PCFs such as ultrahigh birefringence and unique chromatic dispersion, which are almost impossible for the conventional optical fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the flexibility for the cross section design, photonic crystal fibers (PCFs) [1][2][3][4][5][6][7][8][9] have achieved excellent properties in birefringence [10][11][12][13][14][15][16][17][18][19], dispersion [20][21][22][23][24][25][26][27][28][29], single polarization single mode [30][31][32], nonlinearity [33], and effective mode area [34][35][36], and also excellent performances in the applications of fiber sensors [37,38], fiber lasers [39][40][41] and nonlinear optics [42][43][44][45] over the past several years. Large numbers of research papers have highlighted some optical properties of the PCFs such as ultrahigh birefringence and unique chromatic dispersion, which are almost impossible for the conventional optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several highly birefringent (HB) PCFs have been demonstrated to achieve high birefringence up to the order of 0.001, which is one order of magnitude higher than that of the conventional polarization-maintaining fibers (PMFs). Most HB-PCFs are achieved based on the large index contrast of the silica and the air by introducing an asymmetric solid fiber core surrounded by air holes (e.g., using a fiber core with double defect or triple defect of the photonic crystal structure [12][13][14][15]). Several research papers have also shown that the ultrahigh birefringence (up to the order of 0.01) can be achieved by employing elliptical air holes in the fiber cladding [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We can expect the tunable region is larger when PCF with much higher birefringence is employed in the laser cavity. This results in the advantage of the application of the PCF in fiber laser, since PCFs wiht much higher birefringence than conventional fibers have been achieved [15][16][17]. The proposed fiber ring laser can also operate at the mode of dual-wavelength lasing when we carefully adjust the polarization controller.…”
Section: Experimental Setup and Resultsmentioning
confidence: 97%
“…Hydrostatic pressure sensors based on birefringent fibers are not compact since they usually need non-fiber components to detect the pressure-induced phase or use the fiber Sagnac interferometer with a relatively long sensing fiber. PCFs [28][29][30][31][32] are the great success in the history of optical fibers, which have achieved excellent properties in birefringence [33][34][35][36][37][38][39][40], dispersion [41][42][43][44][45][46][47][48][49][50][51], single polarization single mode [52][53][54], nonlinearity [55], and effective mode area [56][57][58], and also excellent performances in the applications of fiber lasers [59][60][61] and nonlinear optics [62][63][64][65] over the past several years. PCFs have also further improved optical fiber sensors and have been used for strain sensing [66], gas sensing [67], biochemical sensing [68], refractive index sensing [69] and temperature sensing [70].…”
Section: Introductionmentioning
confidence: 99%